Pengaruh Kualitas Pelayanan Digital Aplikasi JAKI terhadap Kepuasan Pengguna - Farhan, Muhammad; Nugroho, David Rizar; Ulya, Enden Darjatul; Mulyono, Mulyono (Universitas 45 Surabaya, 2025)
This study analyzes the effect of digital service quality in the Jakarta Kini (JAKI) application on user satisfaction in Jakarta. JAKI, a flagship smart city innovation developed by the Jakarta Provincial Government, functions as an integrated digital public service platform designed to streamline bureaucratic processes, enhance accessibility, and strengthen citizen participation. Using a quantitative approach, questionnaires were distributed to 100 active users who had used JAKI for at least three months. Simple linear regression indicates that digital service quality—comprising ease of use, system reliability, data security, and responsiveness significantly influences user satisfaction (R² = 0.68; p < 0.05). Users report feeling more assisted, satisfied, and comfortable when accessing public services, and responsive digital interactions further reinforce trust in government performance. These findings underscore the critical role of high-quality digital services in shaping positive user experiences, increasing platform adoption, and supporting Jakarta’s broader smart city agenda. The study also provides practical implications for policymakers, including the need to improve inter-agency coordination, strengthen cybersecurity measures, accelerate response times for citizen reports, and optimize user interface design to ensure more efficient, transparent, and user-centered digital public services.